(3JSejW ebUhQI GHf OQjOs - (3GHf OQjO , CHh HcQ eMeO Hf GdMSf Hf OQjO GdCROj, GHf OQjO,J (B321 (3g` s
(3ChdgG (B:s
(3hHYO(B: (3ajbhd GdYHO GdVYja Edi QMeI QHg Gdbhi eP cGf eGdG RGd jNTi chfg hGHjV ef hMa GdYPGd Lhfg bdJ dgG hGdUjQ fOYhfg CeG JQi QCSi MGci dhfg s
(3BNQgG (B:s
(3MGTGi Cf CZTi eOGfi SHI Ch Cf CQi eNJVYG dfcHI ChdG HJgGL aQMG Ch eROgi hGdMeO ddg Ydi GdJeGe hGdceGd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GfXQg eY GdQSGdI GdMGJejIs
(3aQZ ef JSejWgG SfI (B1202 (3ai GdeTgO GdZQhis
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3JSejW TYQi s
Keywords: (3GdCOHs